Time to Talk: Creating Classroom Contexts Where Students Begin to Talk Science (Alberta Journal of Educational Research, 2002)
This study describes and examines how a classroom teacher and a teacher educator create educational contexts where students begin to talk science. Specifically, a grade 6/7 teacher and a teacher educator team planned and team-taught science to 29 students throughout one school year. The study was qualitative in nature, and an ethnographic approach was used in data collection. Through inductive data analysis, distinct opportunities to talk science are identified. Talking science in this study includes small-group unguided talk, large-group guided talk, and open-ended talk with an outside audience. A framework for talking science emerges as a guide for teachers to begin teaching science in ways that allow students time to talk science with their peers and with outside audiences.